Tracing Colonial Entrenchments in the Development of the Central Bank of Sri Lanka - Senthe, Shanthi E. (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2023)
Sri Lanka’s recent tumultuous economic crisis has generated grave uncertainty in the global financial ecosystem. Sri Lanka’s fiscal demise, described as the “canary in the coalmine”, has served as a glaring cautionary tale for financial regulators. The International Financial Institutions continue to warn of subsequent economic fallouts as global debt issues simmer to the surface. Sri Lanka’s economic fallout serves as a story besieged by colonial, political and current geopolitical conditions, which are further compounded by the end of the brutal civil war, foreign debt and post Covid-19 consequences. This paper, however, explores the cracks in the economic foundation using historical moments that paved the legal framework for the emergence of a centralized banking institution. This historical inquiry includes the origins of the financial inclusion discourse in Sri Lanka, which encompasses both colonial and post-colonial temporalities. As a result of Sri Lanka’s fiscal collapse, the Central Bank of Sri Lanka’s role has been under scrutiny. The economic crisis began in 2019, yet the financial regulator’s failure to engage in mitigating tactics to combat the rapid decrease in foreign reserves, rise in sovereign debt, financial mismanagement and political interference is underexplored. In order to further understand how the CBSL, the country’s first financial steward and custodian of fiscal stability, became ineffective, a closer examination of its genesis is made. This paper serves to examine the formation of centralized banking through a particular conceptual goal of ‘financial inclusion’, which catalyzed the establishment of the current central bank structure in Sri Lanka. As such, the financial policies designed and developed crafted by the financial regulator are explored through the lens of financial inclusion.